Pengaruh Kualitas Pelayanan dan Kemampuan Sumber Daya Manusia Terhadap Kesejahteraan Anggota Koperasi Wahidiyah Kecamatan Kedungwaringin - Suripto Moh. Zulkifli; Satim Hamid; Ririn Uke Saraswati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of service quality and human resource capabilities on the welfare of Wahidiyah Cooperative members of Kedungwaringin District, both partially and simultaneously. Quantitative research method with descriptive approach. The population in this study were all cooperative members. The sampling technique used Non Probability Sampling technique with a sample size of 120 people. Data collection using a questionnaire. The data analysis technique used is multiple linear regression analysis, classical assumptions and hypotheses. The results of data quality show all valid and reliable. Partial test results for service quality variables show tcount (7.571)> from ttable (1.980) and sig value 0.00 <0.05 then Ho is rejected and Ha is accepted which means there is a positive and significant influence on member welfare. Partial test results for the human resource capability variable show tcount (15.269)> from ttable (1.980) with a sig value of 0.00 <0.05, so Ho is rejected and Ha is accepted, which means there is a positive and significant influence on member welfare. The test results simultaneously obtained the value of fcount (117.840)> from ftable (3.07) with a sig value of 0.00 <0.05 it can be concluded that H0 is rejected and Ha is accepted, meaning that service quality (X1) and human resource capabilities (X2) together have a significant effect on the welfare of members.